A high-strength aging-resistant PP-R composite material and its preparation method and application
By grafting lignin maleate onto PP-R resin and combining it with treated glass fibers, the problems of anti-aging agent precipitation and low interfacial bonding strength in PP-R composite materials were solved, resulting in PP-R composite materials with high strength and good UV aging resistance.
Patent Information
- Application Number
- CN202311194277.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-09-15
AI Technical Summary
In existing PP-R composite materials, anti-aging agents are prone to precipitation, resulting in poor resistance to ultraviolet aging, and the interfacial bonding strength between PP-R and glass fiber is low.
By grafting lignin maleate onto PP-R resin, a lignin-grafted PP-R material (PPR-g-MAH-Lignin) was prepared and mixed with glass fiber treated with a silane coupling agent to form a high-strength, aging-resistant PP-R composite material, which solved the problems of poor compatibility and low interfacial bonding strength between lignin and PP-R.
It significantly improves the UV aging resistance of PP-R composite materials, enhances the interfacial bonding strength between PP-R and glass fiber, and strengthens the overall performance of the material, especially with a strength retention rate of over 98.5% after UV aging.
Smart Images

Figure BDA0004451743040000041 
Figure BDA0004451743040000091 
Figure BDA0004451743040000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and more specifically to a high-strength aging-resistant PP-R composite material and a preparation method and application thereof. Background Art
[0002] Random copolymer polypropylene (PP-R) is a new type of polymer developed by randomly copolymerizing ethylene monomers into the PP main chain. It has excellent comprehensive performance, but the mechanical strength and aging resistance of PP-R pipes can be further improved to expand its application field. In order to solve the mechanical strength problem of PP-R pipes, people often add reinforcing agents to PP-R materials, such as carbon fiber, asbestos fiber, glass fiber, silicon carbide, etc. Among them, the addition of glass fiber (glass fiber) can significantly improve the mechanical properties of PP-R materials while maintaining the excellent properties of the original resin, such as tensile properties, bending resistance, and impact resistance. Glass fiber is an inorganic non-metallic material with excellent performance. Glass fiber reinforced composite materials have excellent properties such as flame retardancy, high temperature resistance, electrical insulation, high tensile strength, and good chemical stability. PP is a typical semi-crystalline polymer. PP crystallization has an important influence on material properties. Crystallization makes the PP molecular chains more tightly combined, and the yield strength, elastic modulus, surface hardness, etc. of the material are improved accordingly. However, due to the lack of active groups on the surface of glass fiber, the interface bonding strength between glass fiber and resin matrix is low and the interlaminar shear strength is small, which affects the mechanical properties of the composite material and limits the application of this composite material to a certain extent.
[0003] In addition, the relatively unstable helical conformation of PP and the tertiary carbon atoms in the structure are more sensitive to oxidation. From processing to use, it is very easy to generate free radicals under the action of ultraviolet light, which promotes the breakage of PP macromolecules, and generates active free radicals that can further split and branch the entire macromolecular chain and trigger subsequent degradation, which eventually causes PP to age and fail, reducing its life. In order to improve the aging resistance of PP-R materials, it is necessary to add various anti-aging agents to the PP-R raw materials, among which the addition of anti-aging agents delays the aging and degradation of PP-R materials. At present, the anti-aging agents added to PP-R mainly include hindered phenols, phosphorus and sulfur adjuvants. Although these synthetic anti-aging agents have the advantages of good anti-aging performance, thermal stability and good compatibility, due to the influence of various environmental factors or impurity residues during use, the anti-aging agents or decomposition products will migrate out of the PP-R materials, posing a certain threat to human health.
[0004] The prior art discloses a composite PE-PPR toughened pipe and a preparation method thereof, comprising three layers, wherein the inner layer is a heat-resistant and antibacterial polyethylene layer, the middle layer is a light-blocking PPR layer, and the outer layer is a toughened PPR layer; the raw materials of the polyethylene layer include the following components: 100 parts of polyethylene resin masterbatch, 1-10 parts of antibacterial masterbatch; the antibacterial masterbatch includes 40-60 parts of polyethylene resin, 0.5-2 parts of light stabilizer, 2-10 parts of polyethylene wax, 3-5 parts of silane coupling agent, and 20-40 parts of nano antibacterial agent; the raw materials of the light-blocking PPR layer include the following components: 100 parts of random copolymer polypropylene resin masterbatch, 1-10 parts of light-blocking masterbatch; the light-blocking masterbatch includes The raw materials of the toughened PPR layer include the following components: 100 parts of random copolymer polypropylene resin masterbatch, 1-5 parts of color masterbatch and 1-10 parts of toughening masterbatch; the toughening masterbatch includes 40-60 parts of random copolymer polypropylene resin masterbatch, 2-5 parts of β-nucleating agent, 20-30 parts of toughening agent, 5-10 parts of hydrogenated styrene-butadiene-styrene block copolymer, 1-5 parts of ultraviolet absorber, 1-5 parts of light stabilizer, 1-5 parts of antioxidant and 5-10 parts of polymer dispersant. It uses lignin as a light-blocking material and glass fiber as a toughening agent. Although it has good overall mechanical properties, it still needs to add light stabilizers, ultraviolet absorbers and other anti-aging agents, and does not solve the precipitation problem of anti-aging agents, and fails to show good anti-ultraviolet aging effects. In addition, lignin has random agglomeration, and the polar lignin has poor compatibility with the non-polar PP-R, which makes it easy to migrate and precipitate during the use and processing, thereby reducing the anti-aging effect of lignin. PP-R is an organic non-polar molecular chain, which leads to low interfacial bonding strength with glass fiber. Summary of the invention
[0005] The invention aims to overcome the defects and shortcomings of the existing PP-R composite materials, such as the easy precipitation of anti-aging agents, the lack of good anti-ultraviolet aging effect, and the low interface bonding strength between PP-R and glass fiber, and to provide a high-strength anti-aging PP-R composite material. By grafting lignin maleate into PP-R resin, the problems of poor compatibility between lignin and PP-R and easy agglomeration and precipitation are solved, the anti-ultraviolet aging performance of the PP-R composite material is significantly improved, and the interface bonding strength between PP-R and glass fiber is improved.
[0006] Another object of the present invention is to provide a method for preparing a high-strength aging-resistant PP-R composite material.
[0007] Another object of the present invention is to provide a high-strength aging-resistant PP-R composite material for use in the preparation of PP-R pipes.
[0008] Another object of the present invention is to provide a PP-R pipe.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A high-strength aging-resistant PP-R composite material, comprising the following components in parts by weight:
[0011] Lignin grafted PP-R material PPR-g-MAH-Lignin 100 parts, glass fiber 10-35 parts,
[0012] The lignin grafted PP-R material PPR-g-MAH-Lignin is prepared as follows:
[0013] The PP-R resin, lignin maleate and initiator are mixed and dissolved in a solvent, left for 10 to 40 hours to allow the methanol to volatilize, and then melt grafted at 180 to 220°C to obtain PPR-g-MAH-Lignin.
[0014] The mass ratio of PP-R resin, lignin maleate and initiator is 100:30-50:0.3-0.5.
[0015] The initiator of the present invention may be dicumyl peroxide (DCP), and the solvent may be methanol.
[0016] The grafting reaction time of the present invention is preferably 5 to 10 minutes.
[0017] Among them, it should be noted that:
[0018] Lignin is the only aromatic polymer in plants, and its content is second only to cellulose. It has great application potential due to its wide sources, abundant reserves, renewability, and environmental friendliness. The presence of phenolic hydroxyl groups in lignin molecules can effectively remove free radicals and has good anti-aging properties, but lignin has problems such as random agglomeration and poor compatibility with materials, resulting in low anti-aging efficiency and slow free radical removal in materials. The present invention first uses lignin and maleic anhydride to prepare lignin maleate, then grafts lignin maleate into PP-R resin to obtain lignin grafted PP-R material (PPR-g-MAH-Lignin), and then mixes PPR-g-MAH-Lignin, PP-R resin, and glass fiber treated with silane coupling agent to extrude a tube, thereby achieving the purpose of preparing high-strength anti-aging PP-R composite material.
[0019] Grafting lignin onto the PP-R molecular chain by covalent bonding not only solves the compatibility problem between lignin and PP-R resin, but also anchors lignin, thereby enhancing the dispersibility of lignin in PP-R resin and reducing the migration, precipitation and decomposition of lignin.
[0020] By grafting MAH-Lignin onto the PP-R molecular chain, the surface properties of the PP-R resin are improved, making it easier to form chemical bonds with the silane coupling agent. At the same time, transverse crystals are generated at the interface between the glass fiber and the PP-R in the system, making the PP-R and glass fiber more tightly bonded, solving the problem of low interface bonding strength between PP-R and glass fiber.
[0021] The successful rate of lignin grafting was ensured by preparing MAH-Lignin first and then grafting.
[0022] Preferably, the following components are included in parts by weight:
[0023] 100 parts of PPR-g-MAH-Lignin and 20 to 30 parts of glass fiber.
[0024] Preferably, the glass fiber is a glass fiber that has been surface passivated and treated with a silane coupling agent.
[0025] In a specific embodiment, the surface passivation treatment of the glass fiber of the present invention is a high temperature treatment, and the treatment temperature is 300-400°C, more preferably 350°C.
[0026] Through the passivation treatment at 350℃, a dense passivation film can be formed on the surface of the glass fiber, which can improve the surface performance, temperature resistance, corrosion resistance and wear resistance of the glass fiber. Through high temperature treatment, some active functional groups can be introduced on the surface of the glass fiber, which can form chemical bonds with the PPR resin and improve the interfacial bonding strength.
[0027] In a specific embodiment, the lignin maleate of the present invention can be prepared by using existing technology, and can also be preferably prepared by referring to the following method:
[0028] Alkali lignin, maleic anhydride and ethylene glycol dimethyl ether are mixed, stirred and heated to 70-100°C, and refluxed for 5-8 hours to obtain a reaction product, which is purified to obtain lignin maleate.
[0029] The mass ratio of alkali lignin, maleic anhydride and ethylene glycol dimethyl ether is 10:3-5:45-55.
[0030] The synthetic route of lignin maleate is as follows:
[0031]
[0032] Among them, the reflux temperature is more preferably 85°C.
[0033] The reflux reaction time is preferably 6 h.
[0034] Among them, in a specific embodiment, the product purification can be carried out specifically by the following method:
[0035] The reaction product is washed with ethylene glycol dimethyl ether to remove organic impurities and unreacted maleic anhydride to obtain a filtrate and a filter residue, and then the obtained filter residue is dissolved with methanol for 5 to 15 minutes, filtered, and washed with methanol to remove inorganic impurities to obtain a filtrate, and the filtrate is collected and evaporated to obtain a solid, which is washed with water, filtered, and dried to obtain pure lignin maleate.
[0036] The amount of methanol used to dissolve the filter residue is 90-110 mL, and the dissolution temperature is 70-75°C, preferably 74°C.
[0037] The present invention also specifically protects a method for preparing the above-mentioned high-strength and aging-resistant PP-R composite material, comprising the following steps:
[0038] The glass fiber which has been subjected to surface passivation treatment and surface treatment is mixed with PPR-g-MAH-Lignin, and extruded and molded simultaneously by melt grafting reaction in an extruder to obtain a high-strength and aging-resistant PP-R composite material.
[0039] In a specific embodiment, the extrusion temperature is preferably 180-220° C. Controlling the extrusion temperature is beneficial to the tight combination of the entire PP-R and the glass fiber, and the reaction is more complete.
[0040] Among them, the parameters of the extrusion process can be specifically set as follows: the temperatures of each zone of the screw extruder are set to 190°C, 195°C, 200°C, 205°C, 210°C, the head temperature is 200°C, and the melt temperature is 200°C.
[0041] The present invention also specifically protects the use of a high-strength aging-resistant PP-R composite material in the preparation of PP-R pipes.
[0042] The present invention also specifically protects a PP-R pipe, which is prepared from the high-strength and aging-resistant PP-R composite material.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] In the high-strength, aging-resistant PP-R composite material of the present invention, alkaline lignin, a biomass-based material, is selected as an anti-aging agent for PPR, and lignin maleate obtained by reacting alkaline lignin with maleic anhydride is grafted into the PPR matrix to form an anti-aging agent functionalized PPR resin, which will effectively prevent the migration of lignin, greatly improve the anti-aging performance of PPR pipes, and at the same time contribute to the recycling of industrial lignin. The reinforcing component of the glass fiber treated with a coupling agent is reacted with the PPR-g-MAH-Lignin system to promote the formation of chemical bonds between the active polar groups in the PP system and the coupling agent, thereby increasing the interfacial bonding strength between the two, thereby improving the mechanical properties of the PPR pipe.
[0045] The high-strength aging-resistant PP-R composite material of the invention has good strength performance and anti-ultraviolet aging performance. The retention rate of strength performance after ultraviolet aging for 500 hours is above 98.5%, and can be widely used in the preparation of water supply PP-R pipes. DETAILED DESCRIPTION
[0046] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0047] Example 1
[0048] A high-strength aging-resistant PP-R composite material, composed of the following raw materials in parts by weight:
[0049] 100 parts of lignin grafted PP-R material (PPR-g-MAH-Lignin) and 10 parts of glass fiber surface treated with a silane coupling agent.
[0050] The preparation method of glass fiber surface treated with silane coupling agent comprises the following steps: high temperature passivation treatment is performed on the glass fiber at 350°C, and then impregnation is performed with silane coupling agent KH550 to obtain glass fiber surface treated with silane coupling agent.
[0051] The preparation method of the PPR-g-MAH-Lignin comprises the following steps:
[0052] Preparation of lignin grafted PP-R material (PPR-g-MAH-Lignin)
[0053] Weigh 100 parts of PP-R resin, 40 parts of MAH-Lignin, 0.4 parts of DCP and 400 parts of methanol according to their mass.
[0054] First, MAH-Lignin and DCP were dissolved in methanol, and the materials were placed in a stirrer to start mixing. The materials were fully mixed in a high-speed machine. After the methanol evaporated, they were added into the high-speed machine for melt grafting reaction. The reaction temperature was 200°C and the reaction time was 5 to 10 minutes to obtain PPR-g-MAH-Lignin.
[0055] The steps for preparing lignin maleate (MAH-Lignin) are as follows:
[0056] 10g of alkali lignin, 4g of maleic anhydride and 50mL of ethylene glycol dimethyl ether were added to a three-necked flask, heated to 85°C under stirring, reacted for 6h under reflux, cooled to room temperature, filtered, and washed with ethylene glycol dimethyl ether to remove organic impurities and most of the unreacted maleic anhydride. The resulting filter residue and 100mL of methanol were then added to a single-necked flask, dissolved at 74°C for 10min, cooled to room temperature, filtered, and washed with methanol to remove most of the inorganic impurities. The filtrate was then rotary evaporated, and the solid was repeatedly washed with water, filtered, and dried to obtain pure lignin maleate.
[0057] Preparation of high-strength and aging-resistant PP-R composite materials
[0058] 100 parts of PPR-g-MAH-Lignin and 10 parts of surface-treated glass fiber were weighed by mass, and the materials were extruded and molded by melt grafting reaction in an extruder to obtain PP-R pipes. The temperatures of each zone of the screw extruder were set to 190, 195, 200, 205, and 210°C, the die temperature was 200°C, and the melt temperature was 200°C.
[0059] Example 2
[0060] A high-strength aging-resistant PP-R composite material, composed of the following raw materials in parts by weight:
[0061] 100 parts of lignin grafted PP-R material (PPR-g-MAH-Lignin) and 20 parts of glass fiber surface treated with a silane coupling agent.
[0062] The preparation method of glass fiber surface treated with silane coupling agent comprises the following steps: high temperature passivation treatment is performed on the glass fiber at 350°C, and then impregnation is performed with silane coupling agent KH550 to obtain glass fiber surface treated with silane coupling agent.
[0063] The preparation method of the PPR-g-MAH-Lignin comprises the following steps:
[0064] Preparation of lignin grafted PP-R material (PPR-g-MAH-Lignin)
[0065] Weigh 100 parts of PP-R resin, 40 parts of MAH-Lignin, 0.4 parts of DCP and 400 parts of methanol according to their mass.
[0066] First, MAH-Lignin and DCP were dissolved in methanol, and the materials were placed in a stirrer to start mixing. The materials were fully mixed in a high-speed machine. After the methanol evaporated, they were added into the high-speed machine for melt grafting reaction. The reaction temperature was 200°C and the reaction time was 5 to 10 minutes to obtain PPR-g-MAH-Lignin.
[0067] The steps for preparing lignin maleate (MAH-Lignin) are as follows:
[0068] 10g of alkali lignin, 4g of maleic anhydride and 50mL of ethylene glycol dimethyl ether were added to a three-necked flask, heated to 85°C under stirring, reacted for 6h under reflux, cooled to room temperature, filtered, and washed with ethylene glycol dimethyl ether to remove organic impurities and most of the unreacted maleic anhydride. The resulting filter residue and 100mL of methanol were then added to a single-necked flask, dissolved at 74°C for 10min, cooled to room temperature, filtered, and washed with methanol to remove most of the inorganic impurities. The filtrate was then rotary evaporated, and the solid was repeatedly washed with water, filtered, and dried to obtain pure lignin maleate.
[0069] Preparation of high-strength and aging-resistant PP-R composite materials
[0070] 100 parts of PPR-g-MAH-Lignin and 10 parts of surface-treated glass fiber were weighed by mass, and the materials were extruded and molded by melt grafting reaction in an extruder to obtain PP-R pipes. The temperatures of each zone of the screw extruder were set to 190, 195, 200, 205, and 210°C, the die temperature was 200°C, and the melt temperature was 200°C.
[0071] Example 3
[0072] A high-strength aging-resistant PP-R composite material is composed of the following raw materials in parts by weight: 100 parts of PPR-g-MAH-Lignin and 25 parts of glass fibers surface-treated with a silane coupling agent.
[0073] The preparation methods of the glass fiber surface treated with a silane coupling agent, PPR-g-MAH-Lignin, and high-strength aging-resistant PP-R are consistent with those in Example 1.
[0074] Example 4
[0075] A high-strength aging-resistant PP-R composite material is composed of the following raw materials in parts by weight: 100 parts of PPR-g-MAH-Lignin and 35 parts of glass fibers surface-treated with a silane coupling agent.
[0076] The preparation methods of the glass fiber surface treated with a silane coupling agent, PPR-g-MAH-Lignin, and high-strength aging-resistant PP-R are consistent with those in Example 1.
[0077] Comparative Example 1
[0078] A PP-R composite material is composed of the following raw materials in parts by weight: 100 parts of PPR-g-MAH-Lignin.
[0079] The preparation method of the PPR-g-MAH-Lignin comprises the following steps:
[0080] Preparation of lignin grafted PP-R material (PPR-g-MAH-Lignin)
[0081] Weigh 100 parts of PP-R resin, 40 parts of MAH-Lignin, 0.4 parts of DCP and 400 parts of methanol according to their mass.
[0082] First, MAH-Lignin and DCP were dissolved in methanol, and the materials were placed in a stirrer to start mixing. The materials were fully mixed in a high-speed machine. After the methanol evaporated, they were added into the high-speed machine for melt grafting reaction. The reaction temperature was 200°C and the reaction time was 5 to 10 minutes to obtain PPR-g-MAH-Lignin.
[0083] The steps for preparing lignin maleate (MAH-Lignin) are as follows:
[0084] 10g of alkali lignin, 4g of maleic anhydride and 50mL of ethylene glycol dimethyl ether were added to a three-necked flask, heated to 85°C under stirring, reacted for 6h under reflux, cooled to room temperature, filtered, and washed with ethylene glycol dimethyl ether to remove organic impurities and most of the unreacted maleic anhydride. The resulting filter residue and 100mL of methanol were then added to a single-necked flask, dissolved at 74°C for 10min, cooled to room temperature, filtered, and washed with methanol to remove most of the inorganic impurities. The filtrate was then rotary evaporated, and the solid was repeatedly washed with water, filtered, and dried to obtain pure lignin maleate.
[0085] Preparation of PP-R composite materials
[0086] 100 parts of PPR-g-MAH-Lignin were weighed by mass and extruded to obtain PP-R pipes by melt grafting reaction in an extruder. The temperatures of each zone of the screw extruder were set to 190, 195, 200, 205, 210°C, the die temperature was 200°C, and the melt temperature was 200°C.
[0087] Comparative Example 2
[0088] A PP-R composite material is composed of the following raw materials in parts by weight: 100 parts of PP-R resin, 10 parts of lignin, and 10 parts of glass fibers surface-treated with a silane coupling agent.
[0089] The preparation method of glass fiber surface treated with silane coupling agent comprises the following steps: high temperature passivation treatment is performed on the glass fiber at 350°C, and then impregnation is performed with silane coupling agent KH550 to obtain glass fiber surface treated with silane coupling agent.
[0090] Preparation of PP-R composite materials
[0091] 100 parts of PP-R resin, 10 parts of glass fiber surface treated with silane coupling agent, and 10 parts of lignin were weighed by mass, and the materials were extruded and molded by melt grafting reaction in an extruder to obtain PP-R pipes. The temperatures of each zone of the screw extruder were set to 190, 195, 200, 205, and 210°C, the die temperature was 200°C, and the melt temperature was 200°C.
[0092] Comparative Example 3
[0093] A PP-R composite material is composed of the following raw materials in parts by weight: 100 parts of PP-R resin and 10 parts of lignin.
[0094] Preparation of PP-R composite materials
[0095] 100 parts of PP-R resin and 10 parts of lignin were weighed by mass, and the materials were melt-grafted and reacted by an extruder to form a PP-R pipe. The temperatures of the screw extruder zones were set at 190, 195, 200, 205, and 210°C, the die head temperature was 200°C, and the melt temperature was 200°C.
[0096] Results
[0097] The PP-R composite materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were sampled and tested for tensile strength according to standard GB / T 8804.3-2003, sampled and tested for flexural strength according to standard GB / T 9341-2008, and sampled and tested for impact strength according to standard GB / T 18743-2002.
[0098] The test results are shown in Table 1:
[0099] Table 1 Strength performance test of Examples 1 to 4 and Comparative Examples 1 to 3
[0100] Tensile strength MPa Flexural modulus MPa <![CDATA[Impact strength KJ.m -2 > Example 1 38.5 1.97 25.9 Example 2 47.5 2.13 23.2 Example 3 53.1 2.88 16.9 Example 4 59.1 3.66 25.0 Comparative Example 1 22.2 1.50 79.6 Comparative Example 2 35.1 1.75 24.3 Comparative Example 3 28.8 0.83 71.2
[0101] It can be seen from Table 1 above that the high-strength aging-resistant PP-R composite materials prepared in Examples 1 to 4 of the present invention have a tensile strength of 38.5 to 59.1 MPa and a flexural modulus of 1.97 to 3.66 MPa, and have good strength properties.
[0102] The comprehensive mechanical properties of the PP-R composite material of the comparative example are significantly lower than those of the high-strength aging-resistant PP-R composite material of the present invention. Among them, lignin is also added in Comparative Example 2, but it does not adopt the method of grafting lignin onto PP-R, and the strength performance of the PP-R composite material finally obtained is significantly inferior to that of Example 1, indicating that the PPR-g-MAH-Lignin prepared by the grafting method and the glass fiber surface treated with silane coupling agent have better interface bonding strength.
[0103] Since no glass fiber is added in Comparative Examples 1 and 3, the impact performance is better than that of the PP-R composite materials with glass fiber added in Examples 1 to 4.
[0104] The PP-R composite materials obtained in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to a UV aging test according to standard GB / T 16422.3-2014, with an aging time of 500 h. Samples were then prepared according to standard GB / T 8804.3-2003 and their tensile strength and elongation at break after aging were measured. Samples were prepared according to standard GB / T 18743-2002 and their impact strength after aging was measured. The retention rates of various properties after aging were calculated.
[0105] The results are shown in Table 2:
[0106] Table 2. Aging test results of Examples 1 to 4 and Comparative Examples 1 to 3
[0107]
[0108]
[0109] The results show that: (1) the PP-R pipe provided by the present invention has excellent aging resistance. After UV aging, the maximum retention rate of tensile strength is 101.3%, the maximum retention rate of elongation at break is 99.7%, and the maximum retention rate of impact strength is 99.6%.
[0110] (2) The aging resistance of Examples 1 to 4 and Comparative Example 1 is better than that of Comparative Examples 2 and 3, indicating that PPR-g-MAH-Lignin fixes lignin, thereby enhancing the dispersibility of lignin in PP-R resin and reducing the migration, precipitation and decomposition of lignin, thereby effectively exerting the anti-aging effect of lignin.
[0111] The technical performance indicators of the pipe made of the high-strength aging-resistant PP-R composite material provided by the present invention have reached the following static hydraulic strength after testing: no cracking and no leakage at 20°C, 1h, 16.0MPa; no cracking and no leakage at 95°C, 22h, 4.3MPa; longitudinal shrinkage rate: ≤2%; simply supported beam impact: the breakage rate is not more than 10% of the number of samples. The PP-R pipe meets the requirements of standard GB / T 18742.3-2017.
[0112] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A high-strength UV-resistant PP-R composite material, characterized in that: It is composed of the following components by mass: Lignin grafted PP-R material PPR-g-MAH-Lignin 100 parts, glass fiber 10-35 parts, The lignin grafted PP-R material PPR-g-MAH-Lignin is prepared as follows: The PP-R resin, lignin maleate and initiator are mixed and dissolved in a solvent, left for 10 to 40 hours to allow the methanol to volatilize, and then melt grafted at 180 to 220°C to obtain PPR-g-MAH-Lignin. The mass ratio of PP-R resin, lignin maleate and initiator is 100:30-50:0.3-0.
5. Lignin maleate was synthesized by the following method: Alkali lignin, maleic anhydride and ethylene glycol dimethyl ether are mixed, stirred and heated to 70-100°C, and refluxed for 5-8 hours to obtain a reaction product, which is purified to obtain lignin maleate. The mass ratio of alkali lignin, maleic anhydride and ethylene glycol dimethyl ether is 10:3-5:45-55. The initiator is dicumyl peroxide, The glass fiber is a glass fiber that has been surface-passivated and surface-treated with a silane coupling agent. The glass fiber and PPR-g-MAH-Lignin are mixed and subjected to melt grafting reaction and then extruded to obtain a high-strength ultraviolet aging-resistant PP-R composite material, and the extrusion temperature is 180-220°C.
2. The high-strength UV-resistant PP-R composite material according to claim 1, characterized in that: 100 parts of PPR-g-MAH-Lignin and 20 to 30 parts of glass fiber.
3. The high-strength UV-resistant PP-R composite material according to claim 1, characterized in that: The surface passivation treatment temperature is 300-400°C.
4. The high-strength UV-resistant PP-R composite material according to claim 1, characterized in that: The purification steps are: The reaction product is washed with ethylene glycol dimethyl ether to remove organic impurities and unreacted maleic anhydride to obtain a filtrate and a filter residue, and then the obtained filter residue is dissolved with methanol for 5 to 15 minutes, filtered, and washed with methanol to remove inorganic impurities to obtain a filtrate, and the filtrate is collected and evaporated to obtain a solid, which is washed with water, filtered, and dried to obtain pure lignin maleate.
5. A method for preparing the high-strength UV-resistant PP-R composite material according to any one of claims 1 to 4, characterized in that: The steps include: The glass fiber which has been subjected to surface passivation treatment and surface treatment is mixed with PPR-g-MAH-Lignin, and extruded and molded simultaneously by melt grafting reaction in an extruder to obtain a high-strength UV-resistant PP-R composite material.
6. Use of the high-strength UV-resistant PP-R composite material according to any one of claims 1 to 4 in the preparation of PP-R pipes.
7. A PP-R pipe, characterized in that: The high-strength UV-resistant PP-R composite material is prepared from the high-strength UV-resistant PP-R composite material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Corrosion-resistant composite plastic for power supply bracket
CN112143097A
KR1018897440000B1